Hate Speech and Social Disintegration: A Normative Response to the Hadith in the Hermeneutical Study of Muhammad Al-Ghazali - Paizin, Harel Bayu; HD, Ahmad Tri Muslim; Alimin, Muh; Ilyas, Syamsul Ma'arif (Jurnal El-Thawalib, 2025)
The phenomenon of hate speech has become a global epidemic in the digital era, spreading at an extraordinary speed through social media platforms such as Facebook, X, WhatsApp, TikTok, and Instagram. This is a crucial problem that requires a solution to prevent social disintegration in society. The purpose of this article is to identify and examine the normative relevance of hadith as an ethical and practical response to hate speech through the hermeneutics of Muhammad al-Ghazali's hadith. This type of research is qualitative with a phenomenological analysis approach. Primary data sources come from hadith books and secondary data from related journals and books. Data were collected through observation and document study techniques and analyzed using content analysis techniques. The results of this study indicate that al-Ghazali did not view hadith merely as literal texts, but rather as social ethical doctrines oriented towards the goals of sharia, namely maintaining the welfare of the community. His hermeneutics places hadith as a normative foundation that firmly rejects hate speech, because it is considered contrary to the basic principles of Islam such as unity, justice, and human dignity.